Lecturer Engagement: Identifying the Influence of Compensation, Career Path and Self-Efficacy on Private University Lecturers in Medan City - Santi Rizki; Rosmala Dewi; Nagian Toni (Harmony Management: International Journal of Management Science and Business, 2024)
This study aims to determine the effect of compensation, career path, and self-efficacy variables on lecturer engagement in private university lecturers in Medan City. The study uses an associative approach and quantitative methods. The population in this study were all lecturers at private universities in Medan City. The sampling method in this study uses probability sampling method with simple random sampling technique, namely taking sample members from a population that is carried out randomly without regard to the strata in that population, with a sample size of 100 respondents. The research results explain that the variables of compensation, career path, and self-efficacy have a positive and significant influence, both partially and simultaneously, on lecturer engagement. It can be seen that the coefficient of determination adjusted square 0.764 which means 76.4% of the factors that influence lecturer engagement at Private Universities in Medan City can be explained by compensation, career path, self-efficacy and 23.6% of other factors in this study.